Local adaptations of Mediterranean sheep and goats through an integrative approach - Bruno Serranito (Nature Portfolio, 2021)
Abstract Small ruminants are suited to a wide variety of habitats and thus represent promising study models for identifying genes underlying adaptations. Here, we considered local Mediterranean breeds of goats (n = 17) and sheep (n = 25) from Italy, France and Spain. Based on historical archives, we selected the breeds potentially most linked to a territory and defined their original cradle (i.e., the geographical area in which the breed has emerged), including transhumant pastoral areas. We then used the programs PCAdapt and LFMM to identify signatures of artificial and environmental selection. Considering cradles instead of current GPS coordinates resulted in a greater number of signatures identified by the LFMM analysis. The results, combined with a systematic literature review, revealed a set of genes with potentially key adaptive roles in relation to the gradient of aridity and altitude. Some of these genes have been previously implicated in lipid metabolism (SUCLG2, BMP2), hypoxia stress/lung function (BMPR2), seasonal patterns (SOX2, DPH6) or neuronal function (TRPC4, TRPC6). Selection signatures involving the PCDH9 and KLH1 genes, as well as NBEA/NBEAL1, were identified in both species and thus could play an important adaptive role.